Ethnic Chrysalis China's Orochen People and the Legacy of Qing Borderland Administration. - Kim, Loretta E. (Harvard University Studies in East Asian Law Ser., 2019)
"Details the early modern history of the Orochen, an ethnic group that has for centuries inhabited areas along the China-Russia borderland. Traces the evolution of Qing policies toward the Orochen and examines how the impact of political organization in one era endures in the group's social and cultural values" ... Provided by publisher.